2022
DOI: 10.1002/smm2.1100
|View full text |Cite
|
Sign up to set email alerts
|

Live microalgal cells modified by L‐cys/Au@carbon dots/bilirubin oxidase layers for enhanced oxygen reduction in a membrane‐less biofuel cell

Abstract: Electrochemical oxygen reduced reaction (ORR) is a critical element in clean energy development. Despite efforts to enhance gas transfer to the reaction interface, the low solubility of O 2 molecules and slow diffusion rate in liquid electrolyte is still a significant challenge. Herein, we design an artificial outer membrane on microalgal cells, which consists of a carbon dots/bilirubin oxidase (CDs/BOD) ORR catalyst layer and a L-cystine/Au nanoporous O 2 supply layer. O 2 generated by photosynthesis from mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Supramolecular nanovesicles have been extensively utilized to encapsulate drugs, enhance therapeutic efficacy, and reduce side effects in cancer treatment. , The nanovesicles based on host–guest interactions have made great progress and are a unique influence in the construction of stimuli-responsive drug delivery. , They could realize intelligent control of drug release triggered by an endogenous environment and exogenous conditions, such as redox, pH, enzyme, light, temperature, and magnetic field. The intracellular or extracellular stimuli could dynamically and reversibly change host–guest nanosystems’ intermolecular interaction and spatial structures, thus inducing drug release . Subsequently, the multicomponent nanovesicles with organic and inorganic function units have received increasing attention in drug delivery. A large number of organic or inorganic species are used as building blocks to construct multicomponent nanosystems by self-assembly strategies, which endow more surprising properties beyond that of each subcomponent. For example, Hu et al reported the hollow bismuth subcarbonate nanotubes (BNTs) assembled from ultrasmall bismuth subcarbonate nanoclusters and drugs based on hydrophobic interaction, which could realize computed tomography imaging and surprising chemo-radiotherapy to overcome cancer . Since hydrophobic effects are the main driving factor for the construction of multicomponent nanovesicles, more and more organic template molecules are designed and synthesized to mediate self-assembly. , However, it still remains challenging to control the spontaneous process of self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular nanovesicles have been extensively utilized to encapsulate drugs, enhance therapeutic efficacy, and reduce side effects in cancer treatment. , The nanovesicles based on host–guest interactions have made great progress and are a unique influence in the construction of stimuli-responsive drug delivery. , They could realize intelligent control of drug release triggered by an endogenous environment and exogenous conditions, such as redox, pH, enzyme, light, temperature, and magnetic field. The intracellular or extracellular stimuli could dynamically and reversibly change host–guest nanosystems’ intermolecular interaction and spatial structures, thus inducing drug release . Subsequently, the multicomponent nanovesicles with organic and inorganic function units have received increasing attention in drug delivery. A large number of organic or inorganic species are used as building blocks to construct multicomponent nanosystems by self-assembly strategies, which endow more surprising properties beyond that of each subcomponent. For example, Hu et al reported the hollow bismuth subcarbonate nanotubes (BNTs) assembled from ultrasmall bismuth subcarbonate nanoclusters and drugs based on hydrophobic interaction, which could realize computed tomography imaging and surprising chemo-radiotherapy to overcome cancer . Since hydrophobic effects are the main driving factor for the construction of multicomponent nanovesicles, more and more organic template molecules are designed and synthesized to mediate self-assembly. , However, it still remains challenging to control the spontaneous process of self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Evans et al (2021) established that the implementation of oxidoreductase-based biocathodes can improve the electrical power production of MFCs. Furthermore, Qing et al (2022) described a 2.39-fold increase in power output achieved by utilizing a BODbased cathode in MFCs.…”
Section: Introductionmentioning
confidence: 99%